2015
DOI: 10.1371/journal.ppat.1005082
|View full text |Cite
|
Sign up to set email alerts
|

An siRNA Screen Identifies the U2 snRNP Spliceosome as a Host Restriction Factor for Recombinant Adeno-associated Viruses

Abstract: Adeno-associated viruses (AAV) have evolved to exploit the dynamic reorganization of host cell machinery during co-infection by adenoviruses and other helper viruses. In the absence of helper viruses, host factors such as the proteasome and DNA damage response machinery have been shown to effectively inhibit AAV transduction by restricting processes ranging from nuclear entry to second-strand DNA synthesis. To identify host factors that might affect other key steps in AAV infection, we screened an siRNA librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 63 publications
(86 reference statements)
0
33
0
Order By: Relevance
“…Due to the large number of spliceosomal proteins detected in our interactome, which have been shown previously can inhibit AAV transduction 43 , we examined whether a functional relationship exists between spliceosomal genes and HDAC4. We stably knocked down HDAC4 in HEK293T cells by transducing the cells with a lentivirus expressing either a miR-RNAi control or miR-RNAi-HDAC4 sequence, and consistently observed a knockdown of at least 80% (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the large number of spliceosomal proteins detected in our interactome, which have been shown previously can inhibit AAV transduction 43 , we examined whether a functional relationship exists between spliceosomal genes and HDAC4. We stably knocked down HDAC4 in HEK293T cells by transducing the cells with a lentivirus expressing either a miR-RNAi control or miR-RNAi-HDAC4 sequence, and consistently observed a knockdown of at least 80% (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There have previously been two distinct approaches taken to classify the molecules mediating AAV transduction: yeast two-hybrid screens using portions of the capsid as bait 48 and siRNA library screens that assess transduction after disrupting gene expression 43 , 49 , 50 . The interactomes we identified in HEK cells (Supplemental Table 1 ) and whole mouse brain lysates (Supplemental Table 2 ) have minimal overlap with the genes recovered from the yeast two-hybrid screen using mouse liver cDNA as a library, though the authors identified nucleotide binding and intracellular trafficking as key functional categories of AAV interactors, which pathway analysis of our data also identified (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These studies lead to two non-mutually exclusive hypotheses for the differences observed: 1) different splicing events are affected in each spliceosomal mutants and 2) the diverse phenotypes could be due to non-spliceosomal functions of each splicing factor. Indeed, recent studies have found that SF3B1 has some non-splicing functions in responding to various cellular stressors 58,59 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Schreiber et al identified an SF3b component, SF3b7, as a restriction factor for recombinant AAV [93] (Fig. 3).…”
Section: Blocking Adeno-associated Viruses (Aav) Vector Transductionmentioning
confidence: 99%